(untitled) (Педагогіка вищої та середньої школи, 2007)
The article deals with the problem of History teachers’ training under present-day condition of reforming of the system of secondary and higher education in Ukraine. The analysis of collected pedagogic experience is presented and the ways of forming of personality of History teacher are planed.